CD47 expression is critical for CAR T-cell survival in vivo. Issue 3 (14th March 2023) - Beckett, Alex N; Chockley, Peter; Pruett-Miller, Shondra M; Nguyen, Phuong; Vogel, Peter; Sheppard, Heather; Krenciute, Giedre; Gottschalk, Stephen; DeRenzo, Christopher
Abstract : Background: CD47 is an attractive immunotherapeutic target because it is highly expressed on multiple solid tumors. However, CD47 is also expressed on T cells. Limited studies have evaluated CD47-chimeric antigen receptor (CAR) T cells, and the role of CD47 in CAR T-cell function remains largely unknown. Methods: Here, we describe the development of CD47-CAR T cells derived from a high affinity signal regulatory protein α variant CV1, which binds CD47. CV1-CAR T cells were generated from human peripheral blood mononuclear cells and evaluated in vitro and in vivo. The role of CD47 in CAR T-cell function was examined by knocking out CD47 in T cells followed by downstream functional analyses. Results: While CV1-CAR T cells are specific and exhibit potent activity in vitro they lacked antitumor activity in xenograft models. Mechanistic studies revealed CV1-CAR T cells downregulate CD47 to overcome fratricide, but CD47 loss resulted in their failure to expand and persist in vivo. This effect was not limited to CV1-CAR T cells, since CD47 knockout CAR T cells targeting another solid tumor antigen exhibited the same in vivo fate. Further, CD47 knockout T cells were sensitive to macrophage-mediated phagocytosis. Conclusions: These findings highlight that CD47 expression is critical for CAR T-cell survival in vivo and is a 'sine qua non' for successful adoptive T-cell therapy.